MODERN TRENDS IN THE DEVELOPMENT OF INDUSTRIAL CONSTRUCTION IN THE AGRICULTURAL SECTOR - LOBAI, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In modern conditions, the country faces the issue of developing the agrarian sector of the national economy, which requires modern infrastructure for its effective functioning. The importance of industrial construction in the agrarian sector is determined by its key role as a fundamental basis for ensuring the effective functioning of the agro-industrial complex since industrial construction contributes to the creation of modern production facilities that provide a continuous cycle of production, processing, storage and logistics of agricultural products.The publication's purpose is to study and assess the trends in the formation, functioning, and development of industrial construction in the agrarian sector and its significance in complex modern realities.Results. The article examines issues regarding the features, trends in development, and functioning in modern conditions of industrial construction of the agrarian sector of the national economy. The directions of agrarian industrial construction are studied. It is determined that before the start of the full-scale war, Ukraine demonstrated stable development in the construction sector, including in the industrial construction sector, and it is substantiated that the construction industry suffered significant losses due to the war. The volume of manufactured construction products by type, the distribution of manufactured products by type, and the assessment of direct losses to the agricultural and land resources were conducted. The directions of the functioning of industrial construction in martial law conditions and post-war reconstruction of the country were determined. The main trends in the long-term development of industrial construction in the agricultural sector should be the widespread introduction of innovative technologies and digitalization.Conclusions. Agricultural construction is strategically important for Ukraine both in wartime and in the period of post-war reconstruction. Therefore, the reconstruction of the destroyed agricultural infrastructure, the expansion of production for domestic and foreign markets, the decentralization of production and the development of rural communities, environmentally sustainable construction and "green" energy, innovations, and digitalization of agricultural construction will become the basis for the future development of the country and its integration into the world economy.
Keywords: industrial construction; agricultural sector; digitalization; investments; development